Development of a Novel Scaffold of Chitosan, Type IV Collagen and Integrin α3β1 As Alternative Scaffold for Primary Culture of Podocytes - Zárate Triviño, Diana Ginette; Hernández Martínez, Sara Paola; Bollain y Goytia de la Rosa, Juan José; Franco Molina, Moisés Armides; Elizalde Peña, Eduardo; Hernández Villegas, Margarita Idalia; Rangel Ochoa, Gloria Azucena; Rodríguez Padilla, María Cristina (Molecular Diversity Preservation International, 2018)
Loss of podocytes has been a main pathology present in renal diseases; the leak of these specialized cells increases the permeability of the glomerular basal membrane (GMB) and protein release affecting the glomeruli, the main structure of the kidney. The study of different physiopathology mechanism has been a challenge because of the short lifetime of podocytes in vitro. We obtained and characterized composites based on Chitosan (CTS), polyvinyl alcohol (PVA), type IV collagen and integrin α3β1 as a possible application in primary culture of podocytes. Podocytes were extracted from the urine of patients with Idiopathic Nephrotic Syndrome (INS). To evaluate biocompatibility, we assessed cell viability through the lactate dehydrogenase assay. Immunohistochemical staining was used to detect the expression of specific proteins from podocytes such as podocin, and podocalyxin and CD80, a marker of cellular stress. The results showed that our synthesis method promotes the copolymerization of the components in the scaffold. Due to its reactivity, the amine group of chitosan made links with type IV collagen and integrin α3β1. The swelling and degradation tests allowed us to select the material with the best mechanical properties for cellular culture. The expression of podocin and podocalyxin remains the same in the culture of podocytes on the scaffold; in contrast, CD80 expression increased. The viability of podocytes cultured on the CTS/PVA/type IV collagen/integrin α3β1 scaffold increased in comparison to the culture control. Keywords: podocytes; half-life; chitosan; protein expression; scaffold